2017
DOI: 10.1101/183004
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Structural covariance of brain region volumes is associated with both structural connectivity and transcriptomic similarity

Abstract: An organizational pattern seen in the brain, termed structural covariance, is the statistical association of pairs of brain regions in their anatomical properties. These associations, measured across a population as covariances or correlations usually in cortical thickness or volume, are thought to reflect genetic and environmental underpinnings.Here, we examine the biological basis of structural volume covariance in the mouse brain. We first examined large scale associations between brain region volumes using… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 63 publications
(64 reference statements)
2
9
0
Order By: Relevance
“…We note that a consistent finding across multiple studies is that seed-based structural covariance maps are generally bilateral (i.e. homotopic regions tend to have similar structural covariance to seed (Mechelli et al, 2005;Pagani et al, 2016;Yee et al, 2018), reflecting the bilateral patterns of transcriptomic similarity, a major correlate of structural covariance (Yee et al, 2018)). Thus, including both hemispheres would be redundant and would likely give similar results to our findings below.…”
Section: Cortex and Thalamus Definitionssupporting
confidence: 55%
See 2 more Smart Citations
“…We note that a consistent finding across multiple studies is that seed-based structural covariance maps are generally bilateral (i.e. homotopic regions tend to have similar structural covariance to seed (Mechelli et al, 2005;Pagani et al, 2016;Yee et al, 2018), reflecting the bilateral patterns of transcriptomic similarity, a major correlate of structural covariance (Yee et al, 2018)). Thus, including both hemispheres would be redundant and would likely give similar results to our findings below.…”
Section: Cortex and Thalamus Definitionssupporting
confidence: 55%
“…Structural covariance can be computed by correlating the structural properties (such as volumes) of pairs of brain regions across a group of individuals (Lerch et al, 2006;Alexander-Bloch et al, 2013a;Evans, 2013). Previous works have shown that structural covariance is associated with both structural (Lerch et al, 2006;Gong et al, 2012;Yee et al, 2018) and functional (Segall et al, 2012) connectivity, and also captures modes of coordinated growth (Alexander-Bloch et al, 2013b), potentially due to the spatially-coordinated expression of genes (Romero-Garcia et al, 2018;Yee et al, 2018). Similar to structural and functional connectivity, seed-based structural covariance maps have been used to parcellate structures including the striatum (Cohen et al, 2008), insula Kelly et al (2012), and hippocampus Plachti et al (2019).…”
Section: Thalamocortical Structural Covariancementioning
confidence: 99%
See 1 more Smart Citation
“…However, the security of this interpretation rests on the more fundamental assumption that structural correlation measured from MRI data on multiple subjects is a reasonable proxy marker of the average weight of axo-synaptic connectivity between regions . Beyond humans (Gong et al, 2012), there is evidence of such correspondence from animal models (Yee et al, 2017).…”
Section: Relationship To Axo-synaptic Connectivity (And Its Adolescenmentioning
confidence: 99%
“…The identification of structural correlation networks in mice (Pagani et al, 2016) suggests that they might encompass general features of cortical architecture. Specifically, up to 35% variance in structural correlation in mice was explained by a combination of tract-tracingderived structural connectivity, gene expression and distance (Yee et al, 2017), providing a link of the macroscopic structural networks to underlying microscale cortical organisation.…”
Section: Relationship To Axo-synaptic Connectivity (And Its Adolescenmentioning
confidence: 99%